OFERTA Y DESARROLLO TURÍSTICO EN LA PARROQUIA SIMIATUG DEL CANTON GUARANDA PROVINCIA DE BOLÍVAR. - Tibanlombo Caiza, Marcia Beatriz (2019)
This research stands out the importance of tourist development based on the offer of the attractions and providers of tourist services in the Simiatug parish. Since there are places to visit that should be used positively in order to improve the life quality of the location. The research has the proposal of designing the strategy for the Simiatug parish, focusing on the tourist development that allows the improvement of the tourist offer, as a solution alternative for the tourist offer and its relation with the tourist development of the parish in which the failure to provide quality services is shown, as well as an inadequate infrastructure because the authorities do not implement tourist plans and projects, it has led to a low level of tourists, factor which in recent years has been generating a minimum amount of economy in the parish. The strategies for the offer with public and private institutions are proposed, which are planned sequentially in order to achieve the objective of improving the tourist offer by promoting tourist development, though activities on how to improve the services offered by each one of the tourist companies, designing new tourist services for the satesfaction of national and foreign tourist, so that in this way the parish of Simiatug can be known at regional level